Inhabiting Infrastructure - Marion Weiss; Michael A. Manfredi (Oz, 2012)
Rail and subway lines, distribution grids, communications rights-of-way, on and off ramps, highways—these elements of our landscape are no less real or less cultural than the institutions that typically attract the attention of designers and the general public. Larger than life, but part of it, infrastructure has an immediate presence; it shapes our environment and urban life in vital, authentic, and often messy ways.